2019
DOI: 10.1111/1759-7714.12985
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and survival of non‐small cell lung cancer patients after surgery: A comprehensive systematic review and meta‐analysis

Abstract: Background Diabetes mellitus (DM) is one of the most common comorbidities in surgically treated non‐small cell lung cancer (NSCLC) patients and has a negative impact on short‐term outcomes. However, the impact of DM on long‐term survival of such patients remains controversial; therefore, we conducted a comprehensive updated meta‐analysis. Methods We systematically searched relevant studies in PubMed, Embase, Cochrane Library, and Web of Science up to 6 September 2018. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The pooled result demonstrated that preexisting diabetes was a significant negative prognostic factor for NSCLC patients' OS, which was supported by previous studies. 5,7,10) This finding was consistent when studies were limited to those 17) Age, gender, BMI, smoking, histology type, surgical procedure, pathological stage, adjuvant therapy, EGFR Humar et al, 2017 21) Gender, smoking, histology type, ECOG-PS, IGF1R Hershman et al, 2016 28) Age, gender, race, weight loss, LDH, stage IIIB or IV Medaiors et al, 2016 29) Age, gender, smoking, race, BMI, comorbidities, ECOG-PS, pathologic stage, procedure, adjuvant chemotherapy Imai et al, 2015 18) Age, gender, BMI, ECOG-PS, stage, histology, smoking Ahmed et al, 2015 23) Gender, smoking, ethnicity, comorbidities, histology type, stage, ECOG-PS Jeon et al, 2015 19) Tuberculosis, stage, size, visceral pleural invasion, positive margin, pathological stage, LVI, BVI, incomplete resection Inal et al, 2014 30) Age, gender, ECOG-PS, smoking, weight loss, stage, chemotherapy, metastasis Inachina et al, 2014 Age, gender, stage, resection Dhillon et al, 2014 24) Age, gender, smoking, histology Luo et al, 2012 20) Age, gender, smoking, ECOG-PS, BMI, stage, cancer treatment Washington et al, 2012 25) Age, gender, surgical procedure, tumor size, stage, histology, adjuvant chemotherapy, visceral pleural invasion Bartling et al, 2011 27) Age Hatlen et al, 2011 26) Age, gender, histology, stage, smoking, performance status Win et al, 2008 31) Shuttle walk distance Van de Poll-Franse et al, 2007 32) Age, gender, stage, treatment DM: diabetes mellitus; BMI: body mass index; ECOG-PS: Eastern Cooperative Oncology Group performance status; EGFR: epidermal growth factor receptor; IGF1R: insulin-like growth factor-1 receptor; LDH: lactate dehydrogenase; LVI: lymphatic vessel invasion; BVI: blood vessel invasion. adjusting for age and/or stage, and sensitivity analysis confirmed the robustness of the main results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled result demonstrated that preexisting diabetes was a significant negative prognostic factor for NSCLC patients' OS, which was supported by previous studies. 5,7,10) This finding was consistent when studies were limited to those 17) Age, gender, BMI, smoking, histology type, surgical procedure, pathological stage, adjuvant therapy, EGFR Humar et al, 2017 21) Gender, smoking, histology type, ECOG-PS, IGF1R Hershman et al, 2016 28) Age, gender, race, weight loss, LDH, stage IIIB or IV Medaiors et al, 2016 29) Age, gender, smoking, race, BMI, comorbidities, ECOG-PS, pathologic stage, procedure, adjuvant chemotherapy Imai et al, 2015 18) Age, gender, BMI, ECOG-PS, stage, histology, smoking Ahmed et al, 2015 23) Gender, smoking, ethnicity, comorbidities, histology type, stage, ECOG-PS Jeon et al, 2015 19) Tuberculosis, stage, size, visceral pleural invasion, positive margin, pathological stage, LVI, BVI, incomplete resection Inal et al, 2014 30) Age, gender, ECOG-PS, smoking, weight loss, stage, chemotherapy, metastasis Inachina et al, 2014 Age, gender, stage, resection Dhillon et al, 2014 24) Age, gender, smoking, histology Luo et al, 2012 20) Age, gender, smoking, ECOG-PS, BMI, stage, cancer treatment Washington et al, 2012 25) Age, gender, surgical procedure, tumor size, stage, histology, adjuvant chemotherapy, visceral pleural invasion Bartling et al, 2011 27) Age Hatlen et al, 2011 26) Age, gender, histology, stage, smoking, performance status Win et al, 2008 31) Shuttle walk distance Van de Poll-Franse et al, 2007 32) Age, gender, stage, treatment DM: diabetes mellitus; BMI: body mass index; ECOG-PS: Eastern Cooperative Oncology Group performance status; EGFR: epidermal growth factor receptor; IGF1R: insulin-like growth factor-1 receptor; LDH: lactate dehydrogenase; LVI: lymphatic vessel invasion; BVI: blood vessel invasion. adjusting for age and/or stage, and sensitivity analysis confirmed the robustness of the main results.…”
Section: Discussionmentioning
confidence: 99%
“…4) Accumulating epidemiological evidence demonstrated that there was a close link between diabetes and several types of cancer, such as endometrial, breast cancer, and prostate cancer. [7][8][9] Although a recent meta-analysis indicated that DM was an independent unfavorable prognostic factor for patients with surgically treated NSCLC compared with their non-diabetic counterparts, 10) no high-quality systematic review has been conducted recently to test how DM affected NSCLC patients in all stages, since numerous patients with advanced NSCLC were not eligible for surgical treatment. Large amount of relevant studies was published recently, and inconsistent conclusion existed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding the association between DM and postoperative complications have been inconclusive [16][17][18][19][20]. In addition, studies about the relationship between DM and survival in individuals who undergo resection for NSCLC have reported contrasting results [15,16,[21][22][23][24] (S1 Table).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DM is independently a worse prognostic factor for patients with malignancies, such as non‐small cell lung cancer, ovarian cancer, and pancreatic cancer 107‐109 . Thus, further study is needed to clarify whether the development of ICI‐related DM is associated with improved clinical outcomes.…”
Section: Incidence and Epidemiology Of Ici‐related Dmmentioning
confidence: 99%